lo g 3 x − 1 ( x − 2 ) = lo g 9 x 2 − 6 x + 1 ( 2 x 2 − 1 0 x − 2 ) , x = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Similarly solved
Great problem!
We have, lo g ( 3 x − 1 ) ( x − 2 ) = lo g ( 9 x 2 − 6 x + 1 ) ( 2 x 2 − 1 0 x − 2 ) ⟹ lo g ( 3 x − 1 ) ( x − 2 ) = lo g ( 3 x − 1 ) 2 2 x 2 − 1 0 x − 2 ⟹ lo g ( 3 x − 1 ) ( x − 2 ) = lo g ( 3 x − 1 ) ( 2 x 2 − 1 0 x − 2 ) ⟹ x − 2 = 2 x 2 − 1 0 x − 2 ⟹ x 2 − 4 x + 4 = 2 x 2 − 1 0 x − 2 ⟹ x 2 − 6 x − 6 = 0 We can now use the quadratic formula. ⟹ x = 2 6 ± 3 6 + 2 4 ⟹ x = 2 6 ± 6 0 ⟹ x = 3 ± 1 5 But 3 − 1 5 is negative and lo g 3 x − 1 x − 2 is undefined for negative x . ∴ x = 3 + 1 5
Can you please tell me how did you solve: x^2 - 6x - 6?
Problem Loading...
Note Loading...
Set Loading...
lo g 3 x − 1 ( x − 2 ) lo g ( 3 x − 1 ) lo g ( x − 2 ) ⇒ 2 lo g ( x − 2 ) lo g ( x − 2 ) 2 ( x − 2 ) 2 x 2 − 4 x + 4 ⇒ x 2 − 6 x − 6 ⇒ x = lo g 9 x 2 − 6 x + 1 ( 2 x 2 − 1 0 x − 2 ) = lo g ( 9 x 2 − 6 x + 1 ) lo g ( 2 x 2 − 1 0 x − 2 ) = lo g ( 3 x − 1 ) 2 lo g ( 2 x 2 − 1 0 x − 2 ) = 2 lo g ( 3 x − 1 ) lo g ( 2 x 2 − 1 0 x − 2 ) = lo g ( 2 x 2 − 1 0 x − 2 ) = lo g ( 2 x 2 − 1 0 x − 2 ) = 2 x 2 − 1 0 x − 2 = 2 x 2 − 1 0 x − 2 = 0 = 2 6 ± 3 6 + 2 4 = 3 + 1 5
The negative value of x is rejected because lo g 3 x − 1 ( x − 2 ) and lo g 9 x 2 − 6 x + 1 ( 2 x 2 − 1 0 x − 2 ) are not defined.